2015
DOI: 10.1016/j.ygyno.2015.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Imiquimod in cervical, vaginal and vulvar intraepithelial neoplasia: A review

Abstract: Background and Aims:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
64
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 44 publications
0
64
2
2
Order By: Relevance
“…The symptoms all disappeared after discontinuation of imiquimod. In a previous review, De Witte et al showed a higher rate of adverse effects in imiquimod use compared with placebo; however, these adverse effects were less severe than in our study [7]. The most common and severe local and systemic effects reported in literature are summarized in Table 2.…”
Section: Discussioncontrasting
confidence: 41%
“…The symptoms all disappeared after discontinuation of imiquimod. In a previous review, De Witte et al showed a higher rate of adverse effects in imiquimod use compared with placebo; however, these adverse effects were less severe than in our study [7]. The most common and severe local and systemic effects reported in literature are summarized in Table 2.…”
Section: Discussioncontrasting
confidence: 41%
“…As synthetic small molecules, imidazoquinolines can be manufactured cost effectively and at high purity. The TLR7 ligand imiquimod is the active component in the topical cream Aldara ® , approved for human immunotherapeutic use to treat skin cancer and genital warts48. However, use of injected imidazoquinolines as vaccine adjuvants have not progressed beyond clinical testing.…”
mentioning
confidence: 99%
“…Conversely, 5% imiquimod cream promotes antitumoral activity via adaptive immune system activation. Success rates for various lesions have been reported to range from 76.3% to 88.0% 6, 7, 8. However, the safety of long‐term imiquimod use during pregnancy is unknown.…”
Section: Discussionmentioning
confidence: 99%